Pemberdayaan Kelompok Wanita Tani Melalui Pelatihan Desain Poster Digital Untuk Promosi Produk Lokal - Eti Fitri Nurhandayani; Dian Fitriani; Firdaus Firdaus (LPPPM STAI Darul Hikmah Bangkalan, 2025)
This Community Service Activity (PKM) aims to improve the skills of members of the Women Farmers Group (KWT) in Dusun 2, Air Satan Village, in creating digital promotional media through training in poster design using Canva. The main problems faced by the partners include a low understanding of the principles of visual communication design and limited skills in using digital design applications. The training was conducted through material presentations, demonstrations, hands-on practice, and technical assistance from the implementation team. A total of 13 out of 24 KWT members participated in the training and showed great enthusiasm. The results of the satisfaction survey indicated an improvement in the participants' skills. A total of 85% of participants experienced creativity and innovation, 70% experienced an increase in skills, and 62% experienced an increase in knowledge. The activity showed a significant increase in participants' understanding of poster design, color principles, typography, and visual layout. Overall, this program contributed to improving digital literacy and visual promotion skills to support the competitiveness of KWT products in the digital market